Implementasi Gaya Belajar Auditori dalam Pembelajaran Pendidikan Agama Islam di SDN 146 Kayu Laut - Kholidah Nur; Fitria Zalzabila; Inda Royani; Miftahhul Jannah; Mhd Pangidoan; Suci Fitriani Nasution (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to describe the application of auditory learning styles in Islamic Religious Education (PAI) at SDN 146 Kayu Laut. A descriptive qualitative method was employed, using interviews as the primary data collection technique. The findings indicate that the PAI teacher implemented auditory-oriented learning strategies such as lecturing, storytelling, question–answer sessions, group discussions, and memorization activities. Audio media, including religious songs, were also used to enhance student understanding. The implementation of the auditory learning style was found to support students in recalling and comprehending the material more easily, as well as improving their verbal communication skills. Nonetheless, several challenges were identified, including students’ difficulty maintaining focus, boredom with repetitive techniques, and occasional technical issues with audio devices. The teacher addressed these obstacles by increasing student engagement through verbal reflections and interactive discussions. Overall, auditory learning strategies were applied effectively, though additional method variations are still needed to accommodate diverse learning styles.